Equilibrative Nucleoside Transporter 1 (ENT1, SLC29A1) Facilitates Transfer of the Antiretroviral Drug Abacavir across the Placenta - Cerveny, Lukas; Ptackova, Zuzana; Ceckova, Martina; Karahoda, Rona; Karbanova, Sara; Jiraskova, Lucie; Greenwood, Susan L; Glazier, Jocelyn D; Staud, Frantisek (Drug metabolism and disposition: the biological fate of chemicals, 2018)
Abacavir is a preferred antiretroviral drug for preventing mother-to-child human immunodeficiency virus transmission; however, mechanisms of its placental transfer have not been satisfactorily described to date. Because abacavir is a nucleoside-derived drug, we hypothesized that the nucleoside transporters, equilibrative nucleoside transporters (ENTs, SLC29A) and/or Na+-dependent concentrative nucleoside transporters (CNTs, SLC28A), may play a role in its passage across the placenta. To test this hypothesis, we performed uptake experiments using the choriocarcinoma-derived BeWo cell line, human fresh villous fragments, and microvillous plasma membrane (MVM) vesicles. Using endogenous substrates of nucleoside transporters, [3H]-adenosine (ENTs, CNT2, and CNT3) and [3H]-thymidine (ENTs, CNT1, and CNT3), we showed significant activity of ENT1 and CNT2 in BeWo cells, whereas experiments in the villous fragments and MVM vesicles, representing a model of the apical membrane of a syncytiotrophoblast, revealed only ENT1 activity. When testing [3H]-abacavir uptakes, we showed that of the nucleoside transporters, ENT1 plays the dominant role in abacavir uptake into placental tissues, whereas contribution of Na+-dependent transport, most likely mediated by CNTs, was observed only in BeWo cells. Subsequent experiments with dually perfused rat term placentas showed that Ent1 contributes significantly to overall [3H]-abacavir placental transport. Finally, we quantified the expression of SLC29A in first- and third-trimester placentas, revealing that SLC29A1 is the dominant isoform. Neither SLC29A1 nor SLC29A2 expression changed over the course of placental development, but there was considerable interindividual variability in their expression. Therefore, drug-drug interactions and the effect of interindividual variability in placental ENT1 expression on abacavir disposition into fetal circulation should be further investigated to guarantee safe and effective abacavir-based combination therapies in pregnancy.
Keywords: Membrane Transport Proteins; biologický transport; nádorové buněčné linie; Rats; Dideoxynucleosides; dideoxynukleosidy; těhotenství; Biological Transport; Anti-HIV Agents; Rats, Wistar; placenta; Equilibrative Nucleoside Transporter 1; adenosin; Cell Line, Tumor; Placenta; krysa rodu Rattus; membránové transportní proteiny; Nucleosides; ekvilibrační přenašeč nukleosidů 2; ženské pohlaví; Adenosine; zvířata; Humans; nukleosidy; Pregnancy; látky proti HIV; ekvilibrační přenašeč nukleosidů 1; potkani Wistar; proteiny přenášející nukleosidy; Female; Equilibrative-Nucleoside Transporter 2; Nucleoside Transport Proteins; lidé; Animals